Phytoremediation for rehabilitating bauxite-mined sites - Mohamad Zuber, Mohammad Fadhil; Phang, Ing Chia; Zainuddin, Zarina (2020)
Recent industrial revolutions cause bauxite mining activities across the globe to become notably more active. However, ceasing bauxite mining activities left bauxite mining sites barren without any vegetation, causing environmental and health problems, such as dust and red muds. Existing remediation techniques such as physical separation, incineration and chemical precipitation may increase risks of additional contamination or be more costly; thus, there is a need for greener and more feasible method such as phytoremediation. Phytoremediation and revegetation may help to make the barren lands to become green again with lower costs. Researches on phytoremediation technique to solve environmental problems in Malaysia are still limited but show great potentials. Works and researches on phytoremediation for rehabilitating bauxite-mined sites has been success- fully conducted across the world, showing promising futures for barren bauxite mining sites in Malaysia. This study summarizes the general scenario of bauxite mining activities and the potential of phytoremediation, focusing on reclamation of bauxite-mined lands.